A Systematic Literature Review: E-Modules Based on Project-Based Learning to Enhance Students’ Learning Creativity and Critical Thinking Skills - Agus Riyanto; Sarwanto; Bowo Sugiharto (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aims to analyze the contribution of e-modules based on Project-Based Learning to enhance students' learning creativity and critical thinking skills in science learning. The method used is a Systematic Literature Review of national and international articles from 2020 to 2025 obtained through Google Scholar. Based on inclusion and exclusion criteria, 19 articles were selected for analysis in terms of product validity, feasibility of use, e-module characteristics, and effectiveness on learning outcomes. The results showed that E-modules based on Project-Based Learning were considered valid to highly valid by experts, practical for use in the classroom, and capable of increasing students' creativity, participation, motivation, and critical thinking skills at a moderate to high level. The integration of contextual project activities made learning more meaningful, collaborative, and in line with the demands of the Merdeka Curriculum and the strengthening of 21st-century competencies. Theoretically, this study confirms that the combination of digital technology and the Project-Based Learning approach contributes to the development of educational science, particularly in the innovation of e-module-based science teaching materials oriented towards higher-order thinking skills. Thus, E-modules based on Project-Based Learning are recommended as an alternative innovative learning medium that supports the improvement of the quality of the learning process and outcomes for students.